A semiotic analysis of toponymy in classic Sundanese literary texts - Koswara, Dedi; Hermawan, Budi (Indonesian Journal of Applied Linguistics, 2021)
This paper investigates classic Sundanese oral literary text Carita Pantun Sanghyang Jagatrasa (CPSJ) and the manuscript of Wawacan Sanghyang Jagatrasa (WSJ) in terms of (1) the transformation of CPJS from oral into written text, (2) the formal structure of CPJS as a narrative poem and the formal structure of WSJ. The investigation employs oral and written literary text approaches based on Propp (1975), and Lord (1976) to examine the texts. The analysis found that (1) structurally CPJS possesses eight formulas, 13 functions, and seven spheres of actions while WSJ possesses six actant models and three functional models, (2) the transformation of CPSJ from oral literary text to a written text lies on the literary conventions, narrative technique, expressions formula, vocabulary, and sentence constructions, (3) the appearance of universal toponymy and anthroponymy in CPSJ and WSJ can semiotically be perceived as a reflection of the existence of classic Sundanese mythology which links human life, animals, and the environment in a harmonious ecology. Semiotically, the transformation is understood as an effort to preserve the moral values contained in CPJS into WSJ relevant to the situation and condition of Sundanese people’s interest.